2013
DOI: 10.2478/s11532-013-0326-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological characterisation of exhaust particulates from diesel-powered light-duty vehicles

Abstract: Abstract:© Versita Sp. z o.o. Keywords: Diesel exhaust particulates • Ecotoxicity • Kinetic luminescent bacteria test • Direct contact test Institute of Environmental Sciences, University of Pannonia, H-8200 Veszprém, HungaryAndrás Ács, Árpád Ferincz, Anikó Kovács, Beatrix Jancsek-Turóczi, András Gelencsér, Gyula Kiss, Nora Kováts * Short CommunicationDiesel exhaust is one of the major sources of fine and ultrafine particulate matter in urban air. Toxicity of diesel-powered engine emissions has been quite wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…With respect to the studies assessing ecotoxicological effects of combustion particles, either extracts in water or DMSO were used for testing [25, 66-69, 91, 92] or the filters were directly used (either grounded or as inserts in well plates) for exposing the bacteria [7,23,24,90,93].…”
Section: Overview On Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the studies assessing ecotoxicological effects of combustion particles, either extracts in water or DMSO were used for testing [25, 66-69, 91, 92] or the filters were directly used (either grounded or as inserts in well plates) for exposing the bacteria [7,23,24,90,93].…”
Section: Overview On Studiesmentioning
confidence: 99%
“…Most often, they concluded that the effects depend on the particle composition (PAH and/or metal content) and also the particle size (e.g., [10,40,50,52,72]). In detail, about a quarter of the authors declared that the PAH content/the organic fraction is responsible for the observed toxic effects (e.g., [9,11,37,88]), and fewer authors correlate the toxic effects with the inorganic water-soluble fraction (e.g., [54,62]), while some authors concluded that both parts attribute to overall toxicity (e.g., [23,71]). In contrast, four authors could not correlate the PAH content to the observed effects [25,42,57,86].…”
Section: Studies' Conclusion On the Potential Of Combustion-derived Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies proved that optically active CPM has significant ecotoxicological potential Ács et al, 2013). The fact that OACs and ecotoxicity both correlated with the concentration of carbonaceous constituents of CPM also suggests light absorbing carbonaceous particulate matter (LAC) is ecotoxic.…”
Section: Correlations Between the Optical Absorption Response (Oac Anmentioning
confidence: 98%
“…Also, this study was the first to determine correlation between the online measured optical absorption (AAE and OAC) and the offline determined ecotoxicological effect of CPM. Numerous earlier studies showed that optically active fraction of CPM has remarkable impact on human health and earthly ecosystems (Donaldson et al, 1996;Donaldson et al, 2002;Li et al, 2003Li et al, , 2009Verma et al, 2009;Verma et al, 2012;Ács et al, 2013;Túroczi et al, 2012). Based on the found correlations, AAE is proposed to be a possible candidate for first-screening the toxicological potential of LAC.…”
Section: Correlations Between the Optical Absorption Response (Oac Anmentioning
confidence: 99%